Histopathological examination following side-by-side placement of metal stents for malignant hilar biliary obstruction - Hiroshi Nakagawara; Kenji Yamao; Takuji Gotoda; Daiichiro Kikuta; Akinori Takei; Kunio Iwatsuka; Toshimi Takahashi; Masahiro Ogawa; Akihiro Henmi; Makio Kobayashi; Mitsuhiko Moriyama (Society of Gastrointestinal Intervention, 2019)
Background : Endoscopic-guided placement of metal stents for unresectable malignant hilar biliary obstruction (UMHBO) is performed using partial stent-in-stent or side-by-side (SBS) techniques. The latter involves placing sequential stents within the bile duct. Excessive dilation of the bile duct during stent placement can have serious effects on the surrounding organs. Methods : This study details seven cases of SBS placement of 8.0 mm metal stents for UMHBO. Histopathological examinations were performed to identify the effects on the bile duct and surrounding tissues. Results : The mean post-placement diameter of the bile ducts was 13.86 mm, and no compression necrosis or thrombi were observed in surrounding tissues. Cholangitis occurred in five cases, and death occurred as a result of cholecystitis in one case. Conclusion : The use of 8.0-mm stents for SBS is unlikely to have major negative effects on peribiliary tissues and blood vessels. However, post-placement cholecystitis can result in increased mortality; thus, gallbladder drainage should be considered.